All eyes on the price: An assessment of the willingness-to-pay for eyeglasses in rural Burkina Faso - Michael Grimm; Renate Hartwig (Health Economics, 2022)
Vision impairment is the most common disability worldwide and it is untreated in large parts of the developing world. We assess the willingness-to-pay (WTP) for eyeglasses among adults in a resource-poor rural setting. We elicit the WTP using the Becker-DeGroot-Marschak (BDM) method. We combine this approach with a layaway scheme and a video intervention to probe to what extent liquidity constraints and information influence the WTP. Our results show that the average WTP is close to the cost of production for corrective glasses. Nevertheless, we find evidence for information constraints. Our video intervention raises the WTP for corrective glasses by 16 percent. We do not find evidence of screening effects, that is after 6~months, use is unrelated to the initial WTP.
Keywords: 330; Burkina Faso; demand; glasses; information; willingness-to-pay